PERAN PARTAI GERINDRA DALAM REKRUTMEN KETERWAKILAN POLITIK PEREMPUAN PADA PEMILU DPR RI 2019 - Nabilah Qonitah Nur'Aini (2022)
This thesis discusses the role of the Gerindra Party in the recruitment of women's political representation in the 2019 DPR RI legislative elections. This research is based on the phenomenon of the low political representation of women in the Gerindra party which did not reach 30% in parliament in 2019 but the presence of women in the Gerindra party increased. The purpose of this research is to describe the role of the Gerindra party in the recruitment of women's political representation in the 2019 DPR RI legislative election This thesis uses Richard Matland's theory. The method used is a qualitative approach with data collection techniques in the form of semi-structured interviews with three informants from political party administrators and one unelected female candidate from the Gerindra Party. The results of the thesis show that the role of parties in recruitment has an impact on increasing women's political representation in parliament. The final result of this study found that; 1) The low representation of women in parliament is influenced by the current recruitment pattern, 2) In the legislative recruitment process, efforts to increase representation are only limited to meeting quotas. So this study concludes that the low representation of women in parliament occurs because the legislative recruitment process has not prioritized women.